Breast-milk derived potential probiotics as strategy for the management of childhood obesity. (November 2020) - Oddi, S.; Huber, P.; Rocha Faria Duque, A.L.; Vinderola, G.; Sivieri, K.
Graphical abstract: Highlights: Both strains increased the alpha diversity of the microbiota of an obese child. L. plantarum  73a and  B. animalis  subsp.  lactis  INL1 administration reduced the Proteobacteria phylum. The ammonium concentration was significantly reduced by the administration of  L. plantarum  73a alone and combined to  B. animalis  subsp.  lactis  INL1. The taxonomy composition was significantly modified by the supplementation of  L. plantarum  73a and  B. animalis subsp. lactis INL1. Abstract: Obesity and overweight, and their concomitant metabolic diseases, emerge as one of the most severe health problems in the world. Prevention and management of obesity are proposed to begin early in childhood, when probiotics may have a role. The Simulator of the Human Intestinal Microbial Ecosystem (SHIME®), in a dynamic validated in vitro system able to simulate the different parts of the gastrointestinal tract, has proven to be useful in analyzing the human intestinal microbial community. L. plantarum 73a and B. animalis subsp. lactis INL1, two strains isolated from breast milk, were assayed in the SHIME® using the fecal microbiota of an obese child. L. plantarum 73a alone or in combination with B. animalis subsp. lactis INL1 demonstrated survival capacity in the SHIME® system. The administration of both strains increased the alpha diversity of the microbiota and reduced the levels of the phylum Proteobacteria. In particular, the genera Escherichia, Shigella, and Clostridium_sensu_stricto_1 were significantly reduced when both strains were administered. The increase of Proteobacteria phylum is generally associated with the microbiota of obese people. Escherichia and Shigella can be involved in inflammation-dependent adiposity and insulin resistance. L. plantarum  73a supplementation reduced ammonia production. L. plantarum 73a alone or in combination with B. animalis subsp. lactis INL1 are potential probiotic candidates for the management of infant obesity.